Sport and climate change: how will climate change affect sport? - Schneider, Sven; Mücke, Hans-Guido (German journal of exercise and sport research, 2021)
Climate change will have complex consequences for the environment, society, economy and people’s health. The issue of climate change has received comparatively little attention to date in the fields of sports science. Thus, sport-related health risks caused by climate change are discussed and summarized in a conceptual model presented here for the first time. Climate change is associated with the following increases of health-related risks for athletes in particular: Direct consequences caused by extreme temperature and other extreme weather events (e.g. increasing risks due to heatwaves, thunderstorms, floods, lightning, ultraviolet radiation) and indirect consequences as a result of climate-induced changes to our ecosystem (e.g. due to increased air pollution by ozone, higher exposures to allergens, increasing risks of infection by viruses and bacteria and the associated vectors and reservoir organisms). Each aspect is supplemented with advice on the prevention of health hazards. Not only individual athletes but also sports organizations and local clubs will have to respond to the changes in our climate, so that they can appropriately protect both athletes and spectators and ensure a plannable continuation of the sport in the future.